The biological functions of sphingolipids in plant pathogenic fungi. - Xue-Ming Zhu; Lin Li; Jian-Dong Bao; Jiao-Yu Wang; Asen Daskalov; Xiao-Hong Liu; Maurizio Del Poeta; Fu-Cheng Lin (PLoS Pathogens)
Sphingolipids are critically significant in a range of biological processes in animals, plants, and fungi. In mammalian cells, they serve as vital components of the plasma membrane (PM) in maintaining its structure, tension, and fluidity. They also play a key role in a wide variety of biological processes, such as intracellular signal transduction, cell polarization, differentiation, and migration. In plants, sphingolipids are important for cell development and for cell response to environmental stresses. In pathogenic fungi, sphingolipids are crucial for the initiation and the development of infection processes afflicting humans. However, our knowledge on the metabolism and function of the sphingolipid metabolic pathway of pathogenic fungi affecting plants is still very limited. In this review, we discuss recent developments on sphingolipid pathways of plant pathogenic fungi, highlighting their uniqueness and similarity with plants and animals. In addition, we discuss recent advances in the research and development of fungal-targeted inhibitors of the sphingolipid pathway, to gain insights on how we can better control the infection process occurring in plants to prevent or/and to treat fungal infections in crops.